MELAMPAUI NYANYIAN RITUAL DALAM KIDUNG WARGASARI SEBAGAI MEDIA PENDIDIKAN TATTWA HINDU DI BALI - I Putu Yoga Pratama (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2026)
This study aims to examine the meaning of Kidung Wargasari in the piodalan ritual and its function as a medium of Hindu theological education in Bali. The research employed a qualitative approach using observation, interviews, documentation, and literature study. The findings show that Kidung Wargasari functions not only as a ritual chant but also contains theological meanings related to bhakti, harmony of life, and the relationship between sekala and niskala. In addition, the chant serves as a medium of Hindu religious education by transmitting the values of tattwa, susila, and spirituality through ritual traditions. The study also found that modernization has reduced public understanding of the philosophical meanings of the chant. Therefore, preservation and reinterpretation efforts are needed to maintain the relevance of Kidung Wargasari in Balinese Hindu society.